Phospho-S129 Alpha-Synuclein Is Present in Human Plasma but Not in Cerebrospinal Fluid as Determined by an Ultrasensitive Immunoassay - Cariulo, Cristina; Martufi, Paola; Verani, Margherita; Azzollini, Lucia; Bruni, Giordana; Weiss, Andreas; Deguire, Sean M.; Lashuel, Hilal A.; Scaricamazza, Eugenia; Sancesario, Giulia Maria; Schirinzi, Tommaso; Mercuri, Nicola Biagio; et al. (Frontiers in Neuroscience, 2019)
Accumulation and aggregation of misfolded alpha-synuclein is believed to be a cause of Parkinson’s disease (PD). Phosphorylation of alpha-synuclein at S129 is known to be associated with the pathological misfolding process, but efforts to investigate the relevance of this post-translational modification for pathology have been frustrated by difficulties in detecting and quantifying it in relevant samples. We report novel, ultrasensitive immunoassays based on single-molecule counting technology, useful for detecting alpha-synuclein and its S129 phosphorylated form in clinical samples in the low pg/ml range. Using human CSF and plasma samples, we find levels of alpha-synuclein comparable to those previously reported. However, while alpha-synuclein phosphorylated on S129 could easily be detected in human plasma, where its detection is extremely sensitive to protein phosphatases, its levels in CSF were undetectable, with a possible influence of a matrix effect. In plasma samples from a small test cohort comprising 5 PD individuals and 5 age-matched control individuals we find that pS129 alpha-synuclein levels are increased in PD plasma samples, in line with previous reports. We conclude that pS129 alpha-synuclein is not detectable in CSF and recommend the addition of phosphatase inhibitors to plasma samples at the time of collection. Moreover, the findings obtained on the small cohort of clinical plasma samples point to plasma pS129 alpha-synuclein levels as a candidate diagnostic biomarker in PD.